Sexual and Gender Diversity in the Muslim World: History, Law and Vernacular Knowledge - Hamzić, Vanja (I.B. Tauris, 2016)
This book offers a path-breaking historical analysis of the discourses on sexual and gender diversity in, or related to, the Muslim world, as well as an ethnographic account of contemporary Muslims in Lahore, Pakistan, whose pluralist sexual and gender experience defies the disciplinary gaze of both international and state law. It provides a stellar mapping of Islamic jurisprudence, court practice and social developments in Muslim polities and the worlds around them, in reliance on extensive materials written across many centuries in numerous classical and contemporary languages. The central claim of this book is that careful examinations of the legal, social and political genealogies of the Islamic legal tradition (in as much as it addresses human sexual and gender difference) and European law (as expressed, in particular, in its manifold elaborations of human rights), although marred by multiple imperial/colonial projects, can ultimately reveal some salient patterns of insurrectionary vernacular knowledge and discursive practices. The ethnographic narrative of the book documents and interrogates some such practices, while the concomitantly pursued critical historical analysis provides a broader background for understanding their invaluable role. In sum, this book is a revolutionary account of diversity and resistance to hegemonic visions of the self and the communal in Muslim lifeworlds.